Educational Quality Assessment - Manual for Interpreting Intermediate School Reports Grade 7 - Burson, William W.; Pennsylvania State Dept. of Education, Harrisburg. Bureau of Educational Quality Assessment ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This manual is designed to aid the school administrator and staff in the interpretation of Pennsylvania's Educational Quality Assessment Report for Grade Seven. General background information is presented on the ten goals of quality education which include: self esteem; understanding others; basic verbal and math skills; health habits; interest in school; citizenship; creativity; vocational attitude and knowledge; appreciation of human accomplishments; and preparing for a changing world. Also presented are brief descriptors of the development field testing, the normative group and the actual administrative procedures. The use and importance of input variables is described and illustrated in several norm charts. How expected scores are calculated is explained. A replica of a school quality report for a hypothetical seventh grade with important points noted composes the bulk of the manual. The appendix includes: school information form; teacher questionnaire and graph of normal curve with Z-scores and percentile equivalents. (MP)
Educational level discussed: Grade 7.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Affective Objectives; Educational Assessment; Educational Quality; Grade 7.; Guides; Norms; Schools; Scores; State Norms; State Surveys; Test Interpretation; Test Results; State Educational Assessment Programs